Management of islamic education boarding school institution - Deden Herman; Maemunah Sa’diyah; Rofi Wirawan (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
Management of islamic boarding school education Islamic education management is a system for regulating the implementation of education so that it meets the desired targets. Education management will regulate various policies in an education system. Boarding school is one of the educational concepts or one of the modern Islamic schools, which has complete dormitories and facilities to support the progress of education in an Islamic context, and in this school there are qualified teachers to provide his best contribution, and this Islamic boarding does not only discuss Islamic learning but general education as well. The purpose of this article is to provide knowledge and explain everything related to the management of Islamic education at Barding School as a forum for Islamic education. The method used is a literature study method from various sources, journal articles, books, and so on. In improving quality and quality, good management is needed to achieve this goal. However, this does not reduce the existence of the educational institution itself. Boarding Schools are the best alternative for parents to send their children to school in any condition. They not only live for themselves and their families but also have to act for the nation and state. Therefore, the support of the best facilities, quality teaching staff and a conducive environment must be encouraged to achieve the aspirations of the nation's children.